2014
DOI: 10.1111/aas.12307
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal fentanyl decreases the optimal effect site concentration of propofol during spinal anaesthesia

Abstract: The EC50 of the effect-site concentration of propofol for sedation decreased from 1.67 ± 0.28 mcg/ml to 0.87 ± 0.15 mcg/ml with the addition of 25 mcg fentanyl to a spinal anaesthetic in patients undergoing urologic surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
2
0
0
Order By: Relevance
“…The effect-site concentration of propofol at a dose of 3 mg/kg/hr in our study was approximately 1.0 μg/ml at 20 min after administration, reaching 1.3 μg/ml at 60 min after the start of propofol administration. These values seem to agree with the findings of previous reports [ 16 18 ]. The optimal effect-site concentration of propofol has been reported to be 0.87–1.67 μg/ml in patients with spinal anesthesia [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effect-site concentration of propofol at a dose of 3 mg/kg/hr in our study was approximately 1.0 μg/ml at 20 min after administration, reaching 1.3 μg/ml at 60 min after the start of propofol administration. These values seem to agree with the findings of previous reports [ 16 18 ]. The optimal effect-site concentration of propofol has been reported to be 0.87–1.67 μg/ml in patients with spinal anesthesia [ 16 ].…”
Section: Discussionsupporting
confidence: 93%
“…These values seem to agree with the findings of previous reports [ 16 18 ]. The optimal effect-site concentration of propofol has been reported to be 0.87–1.67 μg/ml in patients with spinal anesthesia [ 16 ]. Another clinical study reported that 1.5–2.5 μg/ml administered using target-controlled infusion produced a relatively better result, compared with higher doses (3.0–4.0 μg/ml).…”
Section: Discussionsupporting
confidence: 93%